Organic acid, a virulence factor for pathogenic fungi, causing postharvest decay in fruits. (25th November 2021) - Jiao, Wenxiao; Liu, Xin; Li, Youyuan; Li, Boqiang; Du, Yamin; Zhang, Zhanquan; Chen, Qingmin; Fu, Maorun
Abstract: Decay due to fungal infection is a major cause of postharvest losses in fruits. Acidic fungi may enhance their virulence by locally reducing the pH of the host. Several devastating postharvest fungi, such as Penicillium spp., Botrytis cinerea, and Sclerotinia sclerotiorum, can secrete gluconic acid, oxalic acid, or citric acid. Emerging evidence suggests that organic acids secreted by acidic fungi are important virulence factors. In this review, we summarized the research progress on the biosynthesis of organic acids, the role of the pH signalling transcription factor PacC in regulating organic acid, and the action mechanism of the main organic acid secreted via postharvest pathogenic fungi during infection of host tissues. This paper systematically demonstrates the relationships between tissue acidification and postharvest fungal pathogenicity, which will motivate the study of host–pathogen interactions and provide a better understanding of virulence mechanisms of the pathogens so as to design new technical strategies to prevent postharvest diseases. Abstract : Organic acids secreted by acidic fungi in the growth medium or in the decayed fruit tissue modulate environmental pH and pathogenicity.